Sistema de geração eólica baseado no gerador de indução de rotor bobinado alimentado por tensões desequilibradas - Oliveira, Ítalo André Cavalcanti de (2017)
Due to the increasing wind power participation in the electric power matrixes of various countries, the connection requirements of wind farms to the electrical system have become more demanding in recent years. According to these requirements, wind turbines must remain connected to the network even during certain levels voltage sags and voltage imbalances. Among the wind generation systems, the most commonly used are those based on doubly fed induction generator. However, such system sare sensitive othe power grid disturbances, since the generator statoris directly connected to the grid. Among the different methods in order to minimize such problems, in thisworkisdiscussedacontrolmethodthatactsinacoordinatedmodetodecreasenegativeeffects onwind powersystemcausedbyunbalancedvoltages inthepowergrid. Inthiswork arepresented theinverter connectedtothepowergridandthe doublyfedinductiongeneratormodelsandcontrol strategies that act in reducing oscillations in active or reactive power, or act in eliminating of the current imbalances. The proposed control system is performed on the stationary reference frame and controls the positive and negative sequence components of the currents without decomposition or additional controllers. In this work, the generator limitations are analyzed as a function of the rotor speed and the control strategy used for different levels of imbalance. In order to verify the performance of control system, simulation results with coordinated converters control operations are presented and discussed. Finally, in order to validate the strategies, experimental results obtained for two scenarios of unbalance in the grid voltage are presented.